Effect of femoral canal shape on mechanical stress distribution and adaptive bone remodelling around a cementless tapered-wedge stem. Issue 9 (September 2016) - Oba, M.; Inaba, Y.; Kobayashi, N.; Ike, H.; Tezuka, T.; Saito, T.
Abstract : Objectives: In total hip arthroplasty (THA), the cementless, tapered-wedge stem design contributes to achieving initial stability and providing optimal load transfer in the proximal femur. However, loading conditions on the femur following THA are also influenced by femoral structure. Therefore, we determined the effects of tapered-wedge stems on the load distribution of the femur using subject-specific finite element models of femurs with various canal shapes. Patients and Methods: We studied 20 femurs, including seven champagne flute-type femurs, five stovepipe-type femurs, and eight intermediate-type femurs, in patients who had undergone cementless THA using the Accolade TMZF stem at our institution. Subject–specific finite element (FE) models of pre- and post-operative femurs with stems were constructed and used to perform FE analyses (FEAs) to simulate single-leg stance. FEA predictions were compared with changes in bone mineral density (BMD) measured for each patient during the first post-operative year. Results: Stovepipe models implanted with large-size stems had significantly lower equivalent stress on the proximal-medial area of the femur compared with champagne-flute and intermediate models, with a significant loss of BMD in the corresponding area at one year post-operatively. Conclusions: The stovepipe femurs required a large-size stem to obtain an optimal fit of the stem. The FEA result and post-operative BMD change of the femur suggest that the combination of a large-size Accolade TMZF stem and stovepipe femur may be associated with proximal stress shielding. Cite this article: M. Oba, Y. Inaba, N. Kobayashi, H. Ike, T. Tezuka, T. Saito. Effect of femoral canal shape on mechanical stress distribution and adaptive bone remodelling around a cementless tapered-wedge stem. Bone Joint Res 2016;5:362–369. DOI: 10.1302/2046-3758.59.2000525.